Cellular Mechanism Underlying Hydrogen Sulfide Mediated Epithelial K+ Secretion in Rat Epididymis - Gao, Dong-Dong; Xu, Jia-Wen; Qin, Wei-Bing; Peng, Lei; Qiu, Zhuo-Er; Wang, Long-Long; Lan, Chong-Feng; Cao, Xiao-Nian; Xu, Jian-Bang; Zhu, Yun-Xin; Tang, Yun-Ge; Zhang, Yi-Lin; et al. (Frontiers in Physiology, 2019)
As a novel gasotransmitter, hydrogen sulfide (H2S) elicits various physiological actions including smooth muscle relaxation and promotion of transepithelial ion transport. However, the pro-secretory function of H2S in the male reproductive system remains largely unclear. The aim of this study is to elucidate the possible roles of H2S in modulating rat epididymal intraluminal ionic microenvironment essential for sperm storage. The results revealed that endogenous H2S-generating enzymes cystathionine β-synthetase (CBS) was localized predominantly in epithelial cells whilst cystathionine γ-lyase (CSE) expressed primarily in smooth muscle cells of rat epididymis. The relative expression level of CBS and CSE escalated from caput to cauda regions of epididymis, which was paralleled to the progressively increasing production of endogenous H2S. The effect of H2S on epididymal epithelial ion transportation was investigated by short-circuit current (ISC), in vivo rat epididymal microperfusion and intracellular ion measurement. Our data showed that the H2S induced transepithelial K+ secretion via adenosine triphosphate-sensitive K+ (KATP) channel and large conductance Ca2+-activated K+ (BKCa) channel. Transient receptor potential vanilloid 4 (TRPV4) channel-mediated Ca2+ influx was implicated in the activation of BKCa channel. The in vivo studies further demonstrated that H2S promoted the K+ secretion of rat epididymal epithelium and the. The dyspoiesis of endogenous H2S caused a significant decrease in K+ concentration of cauda epididymal intraluminal fluid. Moreover, our data demonstrated that extracellular K+ actively regulated the motility of cauda epididymal sperm in a pH-independent manner. Collectively, the present study demonstrated that H2S was vital to the formation of high K+ concentration in epididymal intraluminal fluid by promoting the transepithelial K+ secretion, which might contributed to the maintainance of the cauda epididymal sperm in quiescent dormant state before ejaculation.